Adenosine deaminase activities in sera, lymphocytes and granulocytes in patients with cutaneous leishmaniasis - Erel, O; Kocyigit, A; Gurel, MS; Bulut, V; Seyrek, A; Ozdemir, Y (Fundaco Oswaldo Cruz, 1998)
Adenosine deaminase (ADA) activities in sera, lymphocytes and granulocytes in patients with cutaneous leishmaniasis were investigated and compared with control groups. Fifty patients and 50 healthy individuals were studied. The clinical diagnosis was parasitologically confirmed by culture and Giemsa stain. ADA activities were measured by colorimetric method. Serum ADA activities 37.80 +/- 11.90, 18.28 +/- 6.08 IU/L (p<0.0001), lymphocyte specific ADA activities 14.90 +/- 7.42, 8.38 +/- 7.42 U/mg protein (p = 0.04), granulocyte specific ADA activities 1.15 +/- 073, 1.09 +/- 0. 67 U/mg protein (p > 0.05) were found in patients and control groups, respectively. ADA activity increases in some infectious diseases were cell mediated immune mechanisms are dominant. In cutaneous leishmaniasis, lymphokine-mediated macrophage activity is the main effector mechanism. Increase in serum and lymphocyte ADA activities in patients with cutaneous leishmaniasis may be dependent on and reflects the increase in phagocytic activity of macrophages and maturation of T-lymphocytes.
Keywords: adenosine deaminase; leishmaniasis